Evaluation of a Dental Health Education Program for Midwives - Zeliha Asli Ocek, DDS, PhD; Ece Eden, DDS, PhD; Meral Turk Soyer, MD; Meltem CiGeklioglu, MD (Blackwell Synergy, 2003)
The aim of the present study was to evaluate the effect of a dental health program for the midwives in primary health care services in Izmir, Turkey